Hand Carriage of Microorganisms by Students of Federal University of Lafia, Nasarawa State, Nigeria (Lafia Journal of Scientific and Industrial Research, 2023)
Microbes from the body's regular flora and transient microorganisms from the environment are found on human hands. Hands can also be used to spread disease from one person to another, especially among close persons. This study aimed to isolate and identify microorganisms from students' hands and assess the occurrence of these bacteria based on gender, level of study, faculty, and hand area (palm and nails swab). Using the pour plate method, a total of sixty (60) hand swab samples (thirty (30) from both palm and nails) were collected and tested for bacterial and fungal presence. Bacteria isolated were Staphylococcus epidermidis (80.00 %), Staphylococcus aureus (75.00 %), Enterococcus spp (50.00 %), Micrococcus spp (46.67 %), Escherichia coli (45.00 %), Klebsiella spp (45.00 %), Bacillus spp (30.00 %), Salmonella spp (13.33 %) and Streptococcus spp (10.00 %). The fungi isolated were Aspergillus niger (45.00 %), Penicillium spp (23.33 %), Mucor spp (21.67 %), Candida spp (20.00 %) and Saccharomyces spp (15.00 %).  Gender, level of study, faculty, and area of hand swab revealed no statistically significant variation in the presence of numerous bacterial and fungal species at p